P770 Autologous regulatory T cell transfer in patients with refractory ulcerative colitis: Interim report of a phase 1, dose-escalation trial. (30th January 2023) - Voskens, C; Stoica, D; Rosenberg, M; Weidinger, C; Vitali, F; Zundler, S; Ganslmayer, M; Wiesinger, M; Wunder, J; Kummer, M; Siegmund, B; Schnoy, E; et al.
Abstract: Background: Ulcerative colitis (UC) is marked by impaired mucosal homeostasis with predominance of intestinal effector T cells and insufficient expansion of mucosal regulatory T cells (Tregs), thereby providing a scientific rationale for Treg-based immunotherapy in UC. Methods: We developed a protocol to generate large numbers of autologous CD25+ cells under aegis of IL-2, rapamycin and anti-CD3/anti-CD28 expander beads ex vivo from CD25+ precursors derived from peripheral blood cells, intended for clinical use under good manufacturing practice (GMP) conditions. We initiated a single-centre, open-label, fast-track dose-escalation, phase-1 clinical trial with a single adoptive transfer of autologous ex vivo expanded CD4+CD25+CD127−/lo Tregs in patients with refractory UC. The primary objective of the trial was to define safety and the maximum tolerable dose of a single intravenous administration of autologous expanded Tregs according to the fast-track dosing principle. Adoptive transfer was escalated from the starting dose of 0.5×10 6 Tregs/kg body weight to the next dose level (1×10 6, 2×10 6, 5×10 6 and 10×10 6 Tregs/kg body weight) in each consecutive patient, respectively, if no dose-limiting toxicity occurred. We here report interim study data of the first 8 patients that received Treg transfer and were followed up over 12 weeks. There were no changes in concomitant medication during the study period. Results: The 8 patients received 0.5 x10 6 (n=1), 1×10 6 (n=1), 2×10 6 (n=1), 2.8x10 6 (n=1), 5×10 6 (n=1) and 10×10 6 (n=3) Treg/kg body weight, respectively. The patients did not show any dose-limiting toxicity and there were no adverse events related to Treg transfer. 87.5% (7/8) of patients had previously received treatment with at least 2 different substance classes of advanced therapies, such as biologics and JAK inhibitors and the mean Mayo Score (MS) at baseline was 9.1±1.6. The mean modified MS (mMS) dropped significantly from 6.6±1.2 at baseline to 4.5±2.2 at week 4 (p=0.006) and 4.6±2.0 at week 12 (p=0.01). There was reduction of mean faecal Calprotectin levels from 1708±397 µg/g at baseline, to 1411±471 µg/g at week 4 and 919±332 µg/g at week 12. Clinical response was reached by 62.5% (5/8) of patients at week 4 and also week 12. Clinical response predominantly occurred in patients receiving the highest number of 10×10 6 Tregs/kg body weight. Clinical remission was achieved by 12.5% (1/8) of patients at week 4 and also week 12. Conclusion: Autologous regulatory T cell transfer was well tolerated up to the maximal tested dose of 10×10 6 Tregs/kg body weight. Study results suggest that adoptively transferred polyclonal Tregs might be effective in refractory ulcerative colitis, warranting further clinical studies.